Lower eGFR is associated with increased probability of liver fibrosis in Chinese diabetic patients. Issue 5 (17th February 2020) - Wang, Yuying; Yu, Yuetian; Wan, Heng; Chen, Yi; Xia, Fangzhen; Zhang, Wen; Zhang, Kun; Gu, Xinjie; Zhang, Yihao; Lin, Zhiqi; Yu, Yuefeng; Wang, Ningjian; et al.
Abstract: Background: Kidney dysfunction is linked to nonalcoholic fatty liver disease (NAFLD) progression including fibrosis, steatosis, or inflammation. We aimed to explore whether lower levels of estimated glomerular filtration rate (eGFR) was associated with increased probability of liver fibrosis. Methods: Two thousand six hundred eighty‐nine subjects enrolled from Shanghai, China, were included in this study. NAFLD fibrosis score (NFS) was used to risk stratify NAFLD patients for fibrosis. eGFR was used to assess kidney function. The association of eGFR level with elevated NFS, and thus high risk of fibrosis, was analysed by linear regression and multinomial logistic regression. The predictive power of eGFR was evaluated via receiver operating characteristic (ROC) curve. Results: A negative association was found between eGFR and NFS (B = −0.21, 95% CI, −0.37 to −0.04, P = .016). As eGFR quartiles decreased, the prevalence of probable fibrosis increased after adjusting for age, sex, current smoking, waist circumference, duration of diabetes, HbA1c, hypertension, dyslipidaemia, and homeostasis model assessment index of insulin resistance (HOMA‐IR) (Q4: reference; Q3: 1.49, 95% CI, 0.82‐2.71; Q2: 1.88, 95% CI, 0.97‐3.67; Q1: 2.70, 95% CI, 1.36‐5.37, P for trend = .002, 1SD increment: 0.73, 95% CI, 0.58‐0.92). The eGFR level can be an effective indicator in differentiating patients with probable presence of fibrosis from those without (AUROC: 0.71, cut‐off point: 92.78 mL/min/1.73 m 2, P < .001). Conclusions: Lower levels of eGFR were associated with higher NFS and thus greater risk of presence of fibrosis in patients with NAFLD and T2DM. Individuals with NAFLD and diabetes should carefully monitor eGFR and receive regular urinalysis, especially when advanced fibrosis is suspected.